Teaching an Undergraduate Statistics Class in Digital Era - Rohayati, Siti; Agustini, Asrifatun; Abdullah, Ahmad Anis (Proceeding International Conference on Science and Engineering, 2020)
Nowadays technological developments are increasingly creative and tend to move towards digital. Technological developments have a major impact on the process of statistical learning at the University. In addition, many students lack understanding of statistical concepts and do not like statistical learning. In this paper, it is given a way of involving technology in the undergraduate class statistics teaching and what statistical concepts are needed in this digital age. Thus, it is hoped that the teaching of the undergraduate statistics class becomes something interesting and fun.